How science teacher educators reconceptualize writing within their curriculum: A self-study - Shepherd, Stephanie; Schnittka, Christine G.; McVay, Matthew J.; Basgier, Christopher R. (American Journal of STEM Education, 2025)
In this self-study, faculty in a UTeach model teacher preparation program engaged in the process of purposefully designing writing assignments and experiences for preservice teachers majoring in science disciplines. Following an iterative curriculum design process, we designed, tested, and redesigned curricular interventions to improve AUTeach students’ experience so that writing is used effectively to learn, reflect, and develop stronger identities as teachers and scientists. This study involved self-reflection as well as scaffolding writing assignments across all program courses. Authors are in the process of implementing the new writing curriculum and anticipate building a robust dataset through an analysis of student writing artifacts to demonstrate the impact of writing across the curriculum in STEM teacher preparation.